Елементи фіто- та зоопростору в контексті наївної катетеризації світу казок українців і росіян - Дяченко-Лисенко, Л.М. (Мовознавство, 2007)
У статті висвітлюються поняття магічно-містичної партиципації, бриколажу, тотемістичної імажинарності давньої духовної культури, репрезентовані народними казками українців і росіян. Казка, як фактор архаїчної творчої фантазії, є системою фундаментальної маніфестації світу. Елементарні форми казки пояснюються базовими тотемістичними категоріями міфічного світогляду. Тотемні уявлення давніх українців і росіян виконують у казках сюжетотворчу і жанротворчу функції. In the article the notions of magic-mysterious participation brikolage, totemistic imaginarity of the ancient spiritual culture are highlighted. They are represented by the folk fairy-tales of Ukrainians and Russians. A fairy-tale as a factor of archaic creative imagination is a system of fundamental manifestation of the world. The elementary forms of the fairy-tale are explained by the basic totemistic categories of the mysterious view. The totemie imagination of the ancient Ukrainians and Russians perform the plot-making and genre-making functions in the fairy-tales.